2020
DOI: 10.1016/j.bcp.2020.114082
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological activity and NMR solution structure of the leech peptide HSTX-I

Abstract: The role of voltage-gated sodium (Na V ) channels in pain perception is indisputable. Of particular interest as targets for the development of pain therapeutics are the tetrodotoxin-resistant isoforms Na V 1.8 and Na V 1.9, based on animal as well as human genetic studies linking these ion channel subtypes to the pathogenesis of pain. However, only a limited number of inhibitors selectively targeting these channels have been reported. HSTX-I is a peptide toxin identified from saliva of the leech Haemadipsa syl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The leech peptide HSTX-I exerts significant analgesic function by specifically inhibiting Nav1.8 and 1.9 channels [ 28 ]. However, another study suggested that HSTX-I was not a useful lead for development of analgesic Nav1.8 and 1.9 modulators [ 29 ]. The specific inhibitors of Nav1.9 channels need further study.…”
Section: Structure and Function Of Nav19 Channelsmentioning
confidence: 99%
“…The leech peptide HSTX-I exerts significant analgesic function by specifically inhibiting Nav1.8 and 1.9 channels [ 28 ]. However, another study suggested that HSTX-I was not a useful lead for development of analgesic Nav1.8 and 1.9 modulators [ 29 ]. The specific inhibitors of Nav1.9 channels need further study.…”
Section: Structure and Function Of Nav19 Channelsmentioning
confidence: 99%
“…For example, the sylvestin peptide (43 amino acids long, molecular weight 4790.4 Da), isolated and purified from the forest leech ( Haemadipsa sylvestris ), can prolong activated partial thromboplastin time (APTT) without affecting prothrombin time (PT) by inhibiting the biological activities of kallikrein and blood coagulation factor XIIa (FXIIa), thus showing potential in the treatment of ischemic stroke [ 28 ]. Similarly, the HSTX-I peptide, isolated from salivary gland secretions of H. sylvestris , can exert a significant analgesic function by inhibiting voltage-gated sodium (NaV) channels (NaV1.8 and NaV1.9) [ 29 , 30 ]. In addition, the neuropeptide Y-HS (36 amino acids long), isolated and purified from H. sylvestris , contains an amidated C-terminus and exhibits significant inhibitory effects on the production of inflammatory cytokines, such as tumor necrosis factor-α (TNF-α), interferon-γ (IFN-γ), interleukin-6 (IL-6), and monocyte chemotactic protein-1 (MCP-1) [ 31 ].…”
Section: Introductionmentioning
confidence: 99%